Diffusion-Weighted Cranial MR Imaging Findings in a Patient with Hemophagocytic Syndrome - Ozgen, B.; Karli-Oguz, K.; Sarikaya, B.; Tavil, B.; Gurgey, A. (American Journal of Neuroradiology, 2006)
SUMMARY: Hemophagocytic lymphohistiocytosis (HLH) is a rare disorder of the immune system that is associated with frequent involvement of the central nervous system (CNS). The MR imaging and CT findings of the CNS infiltration have been reported in the past; however, the diffusion-weighted imaging (DWI) findings have not been previously described. We present MR imaging findings in a case of secondary HLH with CNS involvement, with an emphasis on the DWI findings.